Development of a Community Advance Care Planning Guides Program and the RELATE Model of Communication. (January 2020) - Candrian, Carey; Lasker Hertz, Susan; Matlock, Daniel; Flanagan, Lierin; Tate, Channing; Kutner, Jean S.; Lum, Hillary D.
Objective: Quality communication is an important aspect of advance care planning (ACP). This study evaluates a certification program that trains lay people in communication skills to support community-based ACP conversations. Methods: The program was developed with an emphasis on communication skills training. The testing of the program included ACP Guides and conversation partners, who were hospice volunteers, to assess the use of communication skills in ACP conversations. The evaluation used direct observations of conversations between trained ACP Guides and conversation partners as well as semi-structured interviews with those trained to become ACP Guides and those participating in the conversation. Results: Twenty-two ACP Guides participated in the testing phase with a retention rate of 100% completing all 4 sessions. The RELATE model of communication emerged during program development and testing. Evaluation of 15 ACP Guides having ACP conversations found that trained ACP Guides could use the RELATE model of communication to support ACP conversations. Conclusion: A community–academic partnership developed an ACP Community Guides Program that trained individuals to have community-based ACP conversations. Next steps include additional testing of the program and RELATE in small numbers, especially among minority populations, to evaluate acceptability and usability of this approach. Practice Implications: Laypersons with concrete communication skills can facilitate effective peer-to-peer ACP conversations.